2021
DOI: 10.6004/jnccn.2020.7619
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability and KRAS Mutation in Stage IV Colorectal Cancer: Prevalence, Geographic Discrepancies, and Outcomes From the National Cancer Database

Abstract: Background: This study sought to assess microsatellite and KRAS status, prevalence, and impact on outcome in stage IV colorectal cancer (CRC). Materials and Methods: The 2010 to 2016 US National Cancer Database was queried for adult patients with stage IV CRC. Prevalence of microsatellite status (microsatellite instability–high [MSI-H] or microsatellite stable [MSS]) and KRAS status (KRAS mutation or wild-type) of the primary CRC was assessed. Overall survival (OS) was evaluated using multivariable Cox proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Colorectal cancer (CRC) is the third most frequent cancer in the world, with 2.0 million new cases in 2020, accounting for 11% of all new cancer cases [ 90 ]. It was estimated as 1.9 million of all new cases and 880,000 deaths in 2018 [ 91 ]. The incidence and mortality rates of colorectal cancer (CRC) differ significantly around the globe, i.e., differs in various regions.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most frequent cancer in the world, with 2.0 million new cases in 2020, accounting for 11% of all new cancer cases [ 90 ]. It was estimated as 1.9 million of all new cases and 880,000 deaths in 2018 [ 91 ]. The incidence and mortality rates of colorectal cancer (CRC) differ significantly around the globe, i.e., differs in various regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported that the BRAF mutation does not influence the response to immunotherapy ( 56 , 57 ), and combination therapy needs to be further explored in large samples. Apart from the BRAF V600E mutation, a common oncogenic mutation is RAS mutation, especially KRAS mutation, which accounts for approximately 40% of CRC cases, and is related to poor prognosis and metastasis ( 58 , 59 ). In addition, the KRAS mutation in CRC is associated with immune suppression and immune infiltration ( 60 , 61 ).…”
Section: How To Make Icis More Effective For Crcmentioning
confidence: 99%
“…As glycolytic phenotype affect the fate of cancer therapy, mutations that alter the cell signaling also influence the strategies targeting energy metabolism. Kirsten Rat Sarcoma viral oncogene homolog gene (KRAS) mutations are frequently observed especially among colon and non-small cell lung cancers [41,42]. Amendola et al, (2019) studied the association of KRAS4A mutations with Warburg-inducing glucose uptake and hexokinases in several cancer cell lines [43].…”
Section: Drug Resistance and Metabolic Targetingmentioning
confidence: 99%